Development and Evaluation of an Anti-Epileptic Oral Fast-Dissolving Film with Enhanced Dissolution and In vivo Permeation - Soroushnai, Arezou; Ganji, Fariba; Vasheghani-Farahani, Ebrahim; Mobedi, Hamid (Current Drug Delivery, 2018)
Objectives: The main objective of this novel study was to develop midazolam hydrochloride fast dissolving oral films (FDFs) using solvent casting method and to evaluate the characteristics of the optimum formulation through in vitro and in vivo analysis. The FDFs are new favorable solid dosage forms that deliver drugs rapidly to the blood circulation system and have great advantages in the emergent control of severe neuropathic attacks in children. Methods: Midazolam nanosuspensions were prepared using the ultrasonic method and then incorporated in the hydroxypropyl methyl cellulose (HPMC)/pullulan polymeric matrix with other excipients like glycerol and cellulose nanofiber as a softener and a compatibilizer, respectively. The prepared films were evaluated for mechanical properties, morphology study, disintegration time, and dissolution time. Results: SEM images of FDFs showed the uniform distribution of spherical nanoparticles in the polymeric matrix. A film with 36% HPMC, 64% pullulan, and 21% glycerin was selected as the optimum formulation by the Design Expert 7 software. The optimum film was stable for three months. Conclusion: The pharmacokinetic parameters of midazolam oral film in comparison to coarse midazolam suspension exhibited significant increase in AUC, Cmax, and a good decrease in Tmax. The overall results showed the enhanced in vivo orotransmucosal absorption of poorly water-soluble drugs via the insertion of drugs nanosuspension in buccal films.
Keywords: buccal film